Fort - DeFelice, Cynthia C. (New York : Farrar Straus Giroux, 2015)
"A middle-grade summer adventure about two boys who build an awesome fort and tangle with two older bullies"--
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Bullying -- Juvenile fiction; Summer -- Juvenile fiction; Great-aunts -- Juvenile fiction; Great-uncles -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Bullying -- Fiction; Summer -- Fiction; Great-aunts -- Fiction; Great-uncles -- Fiction